Application method of Fourier Transform Infrared (FTIR) combined with chemometrics for analysis of rat meat (Rattus Diardi) in meatballs beef - Guntarti, Any; Prativi, Seshilia Rarasati (Pharmaciana, 2017)
Food product forgery begins to become a new problem in Indonesia, the main problem is there is a concern that food product is mixed with forbidden meat, one of may is rat meat in meatball.Â  This study is expected to become one basic in order to meet meatball authenticity guarantee.Study about the utilization of infrared spectrophotometry Fourier Transform (FTIR) which was combined with chemometric was carried out to identified rat meat in meatball quantitative and qualitatively. Concentration variation of beef and rat meat in producing meatball is 0%, 25%, 35%, 65%, 75% and 100% rat meat in meatball dough and 5 samples of market meatball. Beef and rat fat which were contained in meatball was extracted by Soxhlet in temperature â¤ 70oC for 7 hours with n-hexane solvent.Qualitative and quantitative analysis was carried out in wave range 750-1600 cm-1 by using partial least square (PLS) multivariate analysis technique and principal component analysis (PCA). The result of calibration with y = 0,9720x + 1,580, coefficient of determination (R2) = 0,9941, and root mean square error of calibration (RMSEC) value was 1.63%. Validation model with, mean root mean square error of cross validation (RMSECV) value was 1.79%, and root mean square error of prediction (RMSEP) value was 2.60%. Using Principal Component Analysis (PCA), grouping of cow fat and mouse fat in the meatballs successfully.Â